A Multicenter Exploration of Sick Building Syndrome Symptoms in Malaysian Schools: Indoor Pollutants, Microbial Taxa, and Metabolites - Yi Zhang; Yongqi Bu; Yang Chen; Peian Chen; Bingqian Du; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Dan Norbäck; Yun Xia; Xi Fu (Metabolites)
Background: The role of the indoor microbiome in sick building syndrome (SBS) is well-recognized, yet prior studies have been limited to single-center analyses, limiting a broader understanding and applicability of their findings. Methods: We conducted a multicenter indoor microbiome and metabolome investigation for SBS, involving 1139 middle school students across three regions in Malaysia (Johor Bahru, Terengganu, and Penang). Using high-throughput amplicon sequencing and untargeted LC-MS, indoor microbiome and metabolites were characterized from classroom dust samples. Results: The study found that the prevalence of SBS symptoms was high across all three centers (51.0% to 54.6%). Environmental characteristics, including indoor NO2 and CO2 concentrations and total weight of indoor dust, were positively associated with SBS (p < 0.01, linear regression). Curtobacterium in Terengganu was negatively associated with SBS, and Clostridium perfringens in Johor Bahru was positively associated with SBS (p < 0.01, FDR < 0.05). Whereas all identified fungal taxa, including an uncharacterized uc_f_Auriculariaceae_sp., Duportella kuehneroides, and Wallemia mellicola, were positively associated with SBS (p < 0.01, FDR < 0.05) in Johor Bahru and Terengganu. Mediation analysis revealed that the adverse health effects of NO2 on SBS were partially mediated by the increased abundance of uc_f_Auriculariaceae_sp. (p < 0.05, total effect mediated 51.40%). Additionally, potential protective metabolites (S-adenosylmethionine, N-acetylserotonin, sphinganine, 4-hydroxy-2-quinolone, and (2E,4Z,8E)-Colneleic acid) were mainly derived from environmental microorganisms, conferring protective effects against nasal symptoms and tiredness. In contrast, synthetic chemicals were associated with higher SBS symptoms, inducing eye and nasal symptoms. Conclusions: This study emphasizes both the significance of fostering a balanced indoor microbiome/metabolite and the necessity to reduce exposure to deleterious substances, providing new insights for future targeted intervention strategies.